The Influence Of Prosperity And Finacial Performance With Respect To Equalization Funds Of The Government District/City In All Southern Sumatra Regions - Rosmiati ROSMIATI; Khairudin KHAIRUDIN; Felisya Fransisca (Bandar Lampung University, 2015)
The prosperity of the local governments will only be realized if local governments are able to generate revenue (PAD) areas of the original and does not rely on Central Government relief funds in financing the activities of local governments. This study aims to test and prove empirically the influence of prosperity and financial performance with respect to equalization funds of the Government district/city for all Southern Sumatra regions. The Data collection is from a data Report i.e. Secondary Budget Realization of the district/city government for all south Sumatra regions in 2012 which is in www.djpk.depkeu.go.id. The prosperity of local government is measured by the amount of equalization funds measureable by generate revenue (PAD) areas or pendapatan asli daerah (PAD), with the amount of funds for Public allocation of Funds, the Results and the allocation of Special Funds, while the financial performance is measured by the ratio of the independence, the ratio of effectiveness, and efficiency ratios. The analysis used was qualitative analysis through descriptive statistics and quantitative analysis through multiple linear regression, hypothesis testing and coefficient of determination. The test results showed that the prosperity of local government positive effect on the performance of the financial performance of local government and the Fund balance of negative effect on the financial performance of local government performance while simultaneously the prosperity of local governments and equalization funds the positive effect of the financial performance of local government performance.